HUBUNGAN GAYA HIDUP DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI DESA KEDUNGWILUT KECAMATAN BANDUNGKABUPATEN TULUNGAGUNG - Antin Nurul Laeliyah; Sutik Sutik; Cucun Setya Ferdina (CV. Adiba Aisha Amira, 2024)
The total of hypertention sufferer is very increasing every time. The factors cause is life style eating food with greasy, eigerrate, coffee are the factors causing the hypertention happen. The purpose of the research is to know the correlation of life style wityh the hypertention to the old in Kedungwilut village, Bandung subistric, Tulungagung regency. The kind of research was correlation and based the time of research was crossectional. The variable of the research ws life style as the independent variable. The hypertention as the independent variable. The population was all of the old in posyandu in Kedungwilut village, Bandung subdistric, Tulungagung Regency. The total respondents share are 262 persons. The experiment use spearmen rho. The results showed that there is a relationship between life and the incidence of hypertension in the elderly in Kedungwilut Village, Bandung District, Tulungagung Regency (Spearman value = 0.000 <0.01 then Ho is rejected). The correlation coefficient of 0.881 indicates positive with very strong strength. In this study, a positive value means that the better the lifestyle, the more normal blood pressure in the elderly in Kedungwilut Village, Bandung District, Tulungagung Regency.